2014
DOI: 10.3233/ch-131770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training and Mediterranean diet on vascular risk reduction in post-menopausal women

Abstract: This study tested the potential risk-reduction benefits of Mediterranean Diet (MD) and regular exercise training on microvascular activity and cardiorespiratory capacity in postmenopausal women. Fifteen sedentary postmenopausal participants (age = 54.6 ± 3.6) were randomised into either exercise training or exercise combined with following MD for eight-weeks, and were assessed for their cardiorespiratory capacity, and upper-and lower-limb endothelial cutaneous vascular conductance (CVC) test using Laser Dopple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 64 publications
(89 reference statements)
5
36
0
Order By: Relevance
“…Younger participants experienced improvements in a number of CVC parameters similarly, the magnitude of which appeared to be greater than the older individuals. While drawing comparisons with other studies is erroneous given the novelty and specificity of dietary-intervention research, our data reflects those observed elsewhere: Klonizakis et al (2013Klonizakis et al ( , 2014 and Alkhatib and Klonizakis (2014) revealed that the MD, when coupled with exercise, led to greater improvements in endothelium-dependent vasodilation than an exercise-only condition in older sedentary individuals (55 ± 4 years).…”
Section: Discussionsupporting
confidence: 71%
“…Younger participants experienced improvements in a number of CVC parameters similarly, the magnitude of which appeared to be greater than the older individuals. While drawing comparisons with other studies is erroneous given the novelty and specificity of dietary-intervention research, our data reflects those observed elsewhere: Klonizakis et al (2013Klonizakis et al ( , 2014 and Alkhatib and Klonizakis (2014) revealed that the MD, when coupled with exercise, led to greater improvements in endothelium-dependent vasodilation than an exercise-only condition in older sedentary individuals (55 ± 4 years).…”
Section: Discussionsupporting
confidence: 71%
“…It is well established that maintaining NO at adequate levels can reduce risk of CVD as reduced bioavailability of NO leads to a loss of cardio-protective actions and may even elevate the progression of CVD [30]. This is consistent with previous literature in which an increase in endothelial function was observed following the MD [2,12,31]. This suggests that diet is a potential mechanism to improve endothelial function in the younger population.…”
Section: Cutaneous Microvascular Functionsupporting
confidence: 91%
“…The risk of developing cardiovascular disease (CVD) increases with age, but approximately 50% of the adult population and 30% of children are considered at high risk of developing CVD [1]. Additionally, events such as the menopause (which causes a decline in oestrogen, which has detrimental effects on the cardiovascular system), increases the risk of developing CVD in post-menopausal women [2]. CVD affects more than 7 million people in the UK, and the cost of managing cardiovascular diseases in the UK is more than £28 billion per year [3].…”
Section: Introductionmentioning
confidence: 99%
“…Such physical training showed sufficient efficacy in the physical capacity of 197 patients during the early stage of ischemic heart disease, including an increase in the efficiency of cardiac work and work performed volume (+74.3%, p < 0.001) as well as the prolongation of exercise time (+ 31.7%, p < 0.001) (Aronov et al, 2009). Microcirculatory perfusion cardiorespiratory capacity also improved in sedentary postmenopausal participants after MIT for 8 weeks as evidenced by this ventilator threshold: 11.5 ± 2.1 vs. 14.0 ± 3.0 ml kg −1 min −1 , p < 0.05 (Alkhatib and Klonizakis, 2014).…”
Section: Moderate-intensity Exercise and MImentioning
confidence: 69%
“…The lowered risk of cardiovascular events in elderly individuals (age, 66.6 ± 2.1 years) was associated with improving exercise capacity (+ 2.0 ml kg −1 min −1 ) and reducing body fat mass (-2.3%) (Niederseer et al, 2011). Regular moderate-intensity training (MIT) for 8 weeks enhanced exercise tolerance and promoted microcirculatory vascular function in postmenopausal women (Alkhatib and Klonizakis, 2014). In summary, exercise training could improve the physical function and parameters of MI related to aging, indicating that the elderly should adhere to appropriate physical exercise, which is conducive to heart health (as shown in Figure 1).…”
Section: Exercise and Age-related MImentioning
confidence: 99%